2013
DOI: 10.1007/s13191-013-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Abrasion on the Flexural Strength of Glazed and Re-glazed Metal Ceramics: An In Vitro Study

Abstract: The functional surfaces of the porcelain fused to metal fixed partial dentures are often abraded to adjust occlusion, such restorations are often found to fail in service. This study was therefore conducted to study the effect of surface abrasion on flexural strength of glazed porcelain fused to metal samples. It was also the aim of this study to find the effect of re-glazing on flexural strength of abraded samples. A total of ninety glazed porcelain fused to metal bar samples of the dimension 15 mm × 2 mm × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The results of research by Bassir et al [1], Preis et al [6], Yener [18], and Her [24] stated that glazing did not increase the flexural strength, indicating that glazing did not cause changes in the flexural strength of the zirconia samples [3]. The Firing of ceramics after occlusal adjustment also showed the same result did not increase flexural strength [1,26]. The study by Chang [3] and Manawi [19] reported that glazing on the ceramic surface and glazing after grinding increases flexural strength because it can reduce the crack depth and close porosity on the ceramic surface [3][4][5]19].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results of research by Bassir et al [1], Preis et al [6], Yener [18], and Her [24] stated that glazing did not increase the flexural strength, indicating that glazing did not cause changes in the flexural strength of the zirconia samples [3]. The Firing of ceramics after occlusal adjustment also showed the same result did not increase flexural strength [1,26]. The study by Chang [3] and Manawi [19] reported that glazing on the ceramic surface and glazing after grinding increases flexural strength because it can reduce the crack depth and close porosity on the ceramic surface [3][4][5]19].…”
Section: Discussionmentioning
confidence: 94%
“…The goals of clinical procedures carried out in the manufacturing stage of zirconia restorations are to improve aesthetic, natural appearance, and reduce wear on opposing teeth. Finishing and polishing procedures can significantly reduce the surface roughness of ceramics [8,9,15,[26][27][28]. Aravind et al [15] stated that the surface results after finishing and polishing on ceramics were the same as those of auto glazed ceramics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation